1996
DOI: 10.1016/s0092-8674(00)81802-4
|View full text |Cite
|
Sign up to set email alerts
|

Control of Male Sexual Behavior and Sexual Orientation in Drosophila by the fruitless Gene

Abstract: Sexual orientation and courtship behavior in Drosophila are regulated by fruitless (fru), the first gene in a branch of the sex-determination hierarchy functioning specifically in the central nervous system (CNS). The phenotypes of new fru mutants encompass nearly all aspects of male sexual behavior. Alternative splicing of fru transcripts produces sex-specific proteins belonging to the BTB-ZF family of transcriptional regulators. The sex-specific fru products are produced in only about 500 of the 10(5) neuron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
600
0
4

Year Published

2000
2000
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 467 publications
(618 citation statements)
references
References 42 publications
(22 reference statements)
14
600
0
4
Order By: Relevance
“…Sex-specific splicing of dsx and fru depends on the activities of multiple conserved 13-nt ESE elements that are recognized by Tra and Tra2+ Because the dsxRE and fru RE activate the recognition of a 39 and a 59 splice site, respectively, it is possible that certain ESEs recruit more than one spliceosomal component to the exon+ To test this hypothesis, we generated a heterologous pre-mRNA (fru59ss/dsx39ssMS2) gene construct that contains the regulated female-specific fru 59 splice site and the weak female-specific dsx 39 splice site on different exons (Fig+ 1A)+ Because each of these splice sites is poorly recognized in its natural context and limits the efficiency of spliceosome assembly (Ryner & Baker, 1991;Tian & Maniatis, 1992; Heinrichs et al+, Hertel 1998), intron removal from the fru59ss/dsx39ssMS2 construct requires the juxtaposition of two suboptimal splice sites+ In this configuration, the weak female-specific fru 59 splice site in fru59ss/dsx39ssMS2 is activated by its native ESE (fru RE) that contains three 13-nt repeat elements recognized by Tra, Tra2, and an SR protein (Heinrichs & Baker, 1995;Lynch & Maniatis, 1996)+ Similar to the experimental design utilized in previous studies (Graveley & Maniatis, 1998), the weak 39 splice site of dsx in the fru59ss/dsx39ssMS2 construct is activated by specific interactions between MS2-RS fusion proteins and the MS2 binding site located approximately 70 nt downstream of the 39 splice site+ Thus, the design of the fru59ss/dsx39ssMS2 construct permits the independent activation of the fru 59 or the dsx 39 splice sites by the addition of recombinant Tra/Tra2 and/or the MS2-RS fusion protein MS2-RS 9G8 to HeLa cell nuclear cell extracts+ In vitro splicing assays were performed in the presence or absence of saturating amounts of Tra/Tra2 and/or MS2-RS 9G8 to evaluate the splicing efficiency of fru59ss/dsx39ssMS2+ For each set of conditions, the splicing reaction was followed over a period of up to 2 h+ Splicing efficiencies were derived from rate measurements as previously described (Hertel & Maniatis, 1998)+ Although no measurable spliced products were detected in the absence of these recombinant proteins, the addition of either the Transformer or MS2-RS fusion proteins resulted in a small but significant activation over background levels (Fig+ 1B, lanes 1-3)+ Kinetic analysis indicated that each enhancer complex increased intron removal by a factor of at least 10-fold over background levels (Fig+ 1C; Table 1)+ This observation is surprising because it suggests that an ESE located on one exon can positively influence the recognition of a weak splice site on a neighboring exon+ By contrast, constitutive splice sites that conform to consensus sequences without an ESE have no significant influence on weak splice sites of neighboring exons+ For example, the common 39 splice site in fru cannot positively influence recognition of the upstream weak female 59 splice site (Ryner et al+, 1996;Heinrichs et al+, 1998)+ Similarly, the constitutive 59 splice site of dsx exon 3 cannot compensate for the suboptimal 39 splice site of exon 4 (Ryner & Baker, 1991;…”
Section: Splicing Enhancers Act As Synergistic Splice Site Activatorsmentioning
confidence: 98%
“…Sex-specific splicing of dsx and fru depends on the activities of multiple conserved 13-nt ESE elements that are recognized by Tra and Tra2+ Because the dsxRE and fru RE activate the recognition of a 39 and a 59 splice site, respectively, it is possible that certain ESEs recruit more than one spliceosomal component to the exon+ To test this hypothesis, we generated a heterologous pre-mRNA (fru59ss/dsx39ssMS2) gene construct that contains the regulated female-specific fru 59 splice site and the weak female-specific dsx 39 splice site on different exons (Fig+ 1A)+ Because each of these splice sites is poorly recognized in its natural context and limits the efficiency of spliceosome assembly (Ryner & Baker, 1991;Tian & Maniatis, 1992; Heinrichs et al+, Hertel 1998), intron removal from the fru59ss/dsx39ssMS2 construct requires the juxtaposition of two suboptimal splice sites+ In this configuration, the weak female-specific fru 59 splice site in fru59ss/dsx39ssMS2 is activated by its native ESE (fru RE) that contains three 13-nt repeat elements recognized by Tra, Tra2, and an SR protein (Heinrichs & Baker, 1995;Lynch & Maniatis, 1996)+ Similar to the experimental design utilized in previous studies (Graveley & Maniatis, 1998), the weak 39 splice site of dsx in the fru59ss/dsx39ssMS2 construct is activated by specific interactions between MS2-RS fusion proteins and the MS2 binding site located approximately 70 nt downstream of the 39 splice site+ Thus, the design of the fru59ss/dsx39ssMS2 construct permits the independent activation of the fru 59 or the dsx 39 splice sites by the addition of recombinant Tra/Tra2 and/or the MS2-RS fusion protein MS2-RS 9G8 to HeLa cell nuclear cell extracts+ In vitro splicing assays were performed in the presence or absence of saturating amounts of Tra/Tra2 and/or MS2-RS 9G8 to evaluate the splicing efficiency of fru59ss/dsx39ssMS2+ For each set of conditions, the splicing reaction was followed over a period of up to 2 h+ Splicing efficiencies were derived from rate measurements as previously described (Hertel & Maniatis, 1998)+ Although no measurable spliced products were detected in the absence of these recombinant proteins, the addition of either the Transformer or MS2-RS fusion proteins resulted in a small but significant activation over background levels (Fig+ 1B, lanes 1-3)+ Kinetic analysis indicated that each enhancer complex increased intron removal by a factor of at least 10-fold over background levels (Fig+ 1C; Table 1)+ This observation is surprising because it suggests that an ESE located on one exon can positively influence the recognition of a weak splice site on a neighboring exon+ By contrast, constitutive splice sites that conform to consensus sequences without an ESE have no significant influence on weak splice sites of neighboring exons+ For example, the common 39 splice site in fru cannot positively influence recognition of the upstream weak female 59 splice site (Ryner et al+, 1996;Heinrichs et al+, 1998)+ Similarly, the constitutive 59 splice site of dsx exon 3 cannot compensate for the suboptimal 39 splice site of exon 4 (Ryner & Baker, 1991;…”
Section: Splicing Enhancers Act As Synergistic Splice Site Activatorsmentioning
confidence: 98%
“…This sex-specific effect is likely attributable to tank-expressing neurons in the PI, because activating PI neurons in which tank functions produces a similar male-specific effect on sedation. Most sexually dimorphic behavior in flies is mediated by the gene fru, which encodes male-specific protein due to sex-specific splicing (Ryner et al, 1996;Demir and Dickson, 2005;Vrontou et al, 2006). fru has been recently implicated in the regulation of ethanol sedation sensitivity, and activation of fru-expressing neurons in males enhances ethanol sensitivity, similar to the effect of activating tank neurons (Devineni and Heberlein, 2012).…”
Section: Tank-and Fru-expressing Neurons Form Likely Synaptic Connectmentioning
confidence: 99%
“…Another example of a general factor brought under sex-specific control is the fru gene of Drosophila, which encodes a transcription factor of the BTB Zn finger protein family (Ito et al, 1996;Ryner et al, 1996;Baker et al, 2001). Several FRU protein isoforms are generated, some of which are expressed in all or nearly all cells of the CNS of both sexes as well as in many other non-neural tissues.…”
Section: Control Of Male Sexual Behavior By the Sex-determination Systemmentioning
confidence: 99%
“…These behavioral fru mutations selectively affect a FRU protein isoform that is present only in the male. This male protein isoform is encoded by a message splice-isoform that is eliminated in the female by splicing activity of the sex-determination pathway (Ryner et al, 1996) (Fig. 3).…”
Section: Control Of Male Sexual Behavior By the Sex-determination Systemmentioning
confidence: 99%
See 1 more Smart Citation